PRAKTIK JUAL BELI HARTA WARISAN YANG BELUM DIBAGI MENURUT HUKUM ISLAM: (STUDI KASUS DI KECAMATAN PANYABUNGAN BARAT) - Sarmila Hayati, Titi Martini Harahap, (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2021)
Property left by someone who has died reuires arrangements about who is entitled to receive it, how much and how to get it. This role is known as faraidh, which is about the inheritance that Allah has determined through His word and is contained in the Qur’an. Inheritance law in Islam is regulated in a systematic, detailed and full of justice. However, there are some people at West Panyabungan District who delay the implementation of the distribution of inheritance, causing problems, namely the property that has not been divided is used and even sold by one heir whithout the permissions of the other heirs, so it is not in accordance with Islamic Law. The formulation of the problem in this study is how the practice of buying and selling inheritance that has not been divided and how the views of Islamic Law of the practice of buying and selling property at West Panyabungan District. This research is a field research whit a qualitative approach. The data sources used are primary data sources obtained directly from the field, namely observation and interviews with the community who are the perpetrators of buying and selling inheritance that has not been divided as well as related heirs and other related informants. Primary data sources obtained from various books, articles, journals and other information related to the discussion theme. The results of the study show that the practice of buying and selling inheritance that has not been divided in West Panyabungan District has been going on for a long time because in fact when someone dies the heirs do not directly distribute the inheritance even decades later, causing internal conflict within the family. Then the view of Islamic Law on this practice is invalid because it does not comply with the terms and pillars of buying and selling, among which the goods being traded are private property and in this inheritance that has not been divided it is still shared property.